Vegetation Warming and Greenness Decline across Amazonia during the Extreme Drought of 2023 - Jiménez, Juan Carlos; Miranda, Vitor; Trigo, Isabel; Libonati, Renata; Albuquerque, Ronaldo; Peres, Leonardo F.; Espinoza, Jhan-Carlo; Marengo, José Antonio [UNESP] (MDPI, 2024)
In 2023, most parts of the world experienced exceptional heat. In particular, anomalous warm temperatures and heatwave events were evidenced across South America during the second half of the year. The situation was particularly critical in the Amazon region in terms of not only hydrometeorological drought but also ecological and socioeconomic impacts. In this study, remote-sensing data collected from the Moderate Resolution Imaging Spectroradiometer (MODIS) were used to observe the changes in temperature and vegetation across Amazonia during the exceptional drought of 2023. This analysis was based on anomalies in the land surface temperature (LST) and vegetation indices: the enhanced vegetation index (EVI) and the normalized difference vegetation index (NDVI). The amplitude of the LST (AMP-LST), an indicator of the energy partitioning between the latent and sensible heat flux, and fire counts were also considered. The results show widespread and extreme warming across Amazonia during the austral spring in 2023, accompanied by a decline in vegetation greenness, water stress conditions across northern Amazonia, and an enhanced fire occurrence across central and northern Amazonia.
Keywords: Amazonia; drought; MODIS; temperature; vegetation